SIRT2 induces the checkpoint kinase BubR1 to increase lifespan. (13th May 2014) - North, Brian J; Rosenberg, Michael A; Jeganathan, Karthik B; Hafner, Angela V; Michan, Shaday; Dai, Jing; Baker, Darren J; Cen, Yana; Wu, Lindsay E; Sauve, Anthony A; van Deursen, Jan M; Rosenzweig, Anthony; et al.
Abstract Mice overexpressing the mitotic checkpoint kinase gene BubR1 live longer, whereas mice hypomorphic for BubR1 (BubR1H/H) live shorter and show signs of accelerated aging. As wild‐type mice age, BubR1 levels decline in many tissues, a process that is proposed to underlie normal aging and age‐related diseases. Understanding why BubR1 declines with age and how to slow this process is therefore of considerable interest. The sirtuins (SIRT1‐7) are a family of NAD+‐dependent deacetylases that can delay age‐related diseases. Here, we show that the loss of BubR1 levels with age is due to a decline in NAD+ and the ability of SIRT2 to maintain lysine‐668 of BubR1 in a deacetylated state, which is counteracted by the acetyltransferase CBP. Overexpression of SIRT2 or treatment of mice with the NAD+ precursor nicotinamide mononucleotide (NMN) increases BubR1 abundance in vivo. Overexpression of SIRT2 in BubR1H/H animals increases median lifespan, with a greater effect in male mice. Together, these data indicate that further exploration of the potential of SIRT2 and NAD+ to delay diseases of aging in mammals is warranted.